Identifikasi Konsentrasi Spasial Industri Kecil Dan Menengah Kabupaten Sragen - Damayanti, Novita (2017)
This study aims to determine the spatial patterns of small and medium industries featured in Sragen. This study uses secondary data, such as the number of business units, the number of workers and the population of this study using analysis tools featured Industrial identification (publications DISPERINKOP and UMKM Sragen), SIG and labor concentration (CI). Based on the analysis that has been done is; The results of the identification of seed industry in Sragen has 8 leading industrial sector based code ISIC yaitu ISIC 10, ISIC 13, ISIC 14, ISIC 16, ISIC 21, ISIC 23, ISIC 31, ISIC 33, the results of the analysis of spatial concentration of industry business units of small and medium Sragen highest concentrations found in the District Plupuh and Masaran. The highest concentration of workers of small and medium industry in Sragen found on the District Plupuh and Masaran. The region has a very high unit distribution businesses located in the area: Tanon, Sragen, Karangmalang, Sambungmacan, Plupuh, Masaran, Kalijambe, Mondokan, Gondang, Gemolong. The region has a very high distribution located in the area: Masaran, Plupuh, Kalijambe Tanon, Mondokan, Sidoharjo, Karangmalang, Sambungmacan, Gondang, Gemolong. The results of the analysis of index of employment (CI) concentration leading industry in Sragen, explained that the highest concentration of industrial workers featured in Sub Gesi, Karangmalang, Masaran, Sambirejo, Sambungmacan, Sragen, Tanon Gondang, Kalijambe, Plupuh, Gemolong, kedawung, Mondokan , Sukodono, Ngrampal, Sidoharjo.